The Monetization of Misogyny: Platform Capitalism and Manosphere's Political Economy - Annisa Nadhifa Ramadhani (Universitas Jenderal Ahmad Yani, 2026)
Contemporary research often views the Manosphere as a cultural backlash or a masculinity crisis. This study reinterprets it as a political and economic system rooted in platform capitalism. Using International Political Economy, it explores how algorithms, affiliate marketing, and multi-level marketing profit from misogynistic radicalization. The analysis of Andrew Tate's